PENGARUH PENAMBAHAN KAYU MANIS PADA TEH BUNGA TELANG TERHADAP KARAKTERISTIK KIMIA DAN ORGANOLEPTIK - Endang Lestari; A. Nova Zulfahmi; Rois Indriawan; Nurimansyah; Ira Arianti (PPPM POLTESA, 2026)
Butterfly pea flower (Clitoria ternatea) is a herbal plant containing various bioactive compounds, including anthocyanins and flavonoids, which have potential applications in functional food products. This study examined the effect of different proportions of butterfly pea flower in herbal teabag formulations on physicochemical properties, specifically moisture content and ash content, as well as sensory acceptance in terms of color, aroma, and taste. The experiment was arranged using a Completely Randomized Design (CRD) with a single factor, namely the proportion of butterfly pea flower at five levels (0%, 25%, 50%, 75%, and 100%), each conducted in triplicate. The collected data were analyzed using analysis of variance followed by a post hoc comparison test at a 95% confidence level. The results indicated that increasing the proportion of butterfly pea flower significantly affected the moisture content of the product (p < 0.05), with values ranging from 12.39% to 14.83%. In contrast, ash content was not significantly influenced by the treatments (p > 0.05), with values ranging from 4.21% to 4.47%, all of which met the requirements of SNI 3836:2013. Sensory evaluation revealed no significant differences among treatments in terms of color, aroma, and taste, with relatively similar hedonic scores across all samples. Overall, the formulation containing 75% butterfly pea flower was considered the most optimal, as it resulted in the lowest moisture content, stable ash content, and higher color acceptance compared to other treatments.